DISPARITAS HAK-HAK PROFESI SECURITY YANG TERIKAT PERJANJIAN KERJA WAKTU TERTENTU - Sudibyo Aji Narendra Buwana; Dahri Haji Dahlan; Hardi Fardiansyah; Nanda Dwi Rizkia (The Juris, 2023)
Workers' rights are one of the human rights. The type of research used by researchers in this study is empirical-juridical. The research approach used is empirical. Data collection techniques using in-depth interviews and observation All primary and secondary data in this study were collected and analyzed qualitatively. The results of his research show that there is a disparity in the rights of women workers. The conclusion is that the disparity in the rights of the security profession that is bound by fixed time work agreement that has been fulfilled at PT Jaguar Inti Perkasa is the provision of wages based on the city minimum wage, the provision of Holy Day Allowance rights, menstrual/menstrual leave rights, maternity leave rights, miscarriage leave rights, annual leave rights, permission to leave work with get wages, the right to occupational safety and health, the right to get the benefits of Institution of Social Security employment, the right to guarantee health care; While the disparity in the rights of workers bound by fixed time work agreements that have not been fulfilled is that they have not been given fixed time work agreement compensation money, there are no private regulations contained in company regulations governing the right to special facilities at certain hours for women workers, there are no provisions governing shift work hours for women workers, and there is no specific provision that regulates that women workers whose children are still breastfeeding must be given proper opportunities to breastfeed their children.